2017
DOI: 10.3747/co.24.3512
|View full text |Cite
|
Sign up to set email alerts
|

User Survey of Nanny Angel Network, a Free Childcare Service for Mothers with Cancer

Abstract: PurposeThe purpose of the present study was to determine user satisfaction with Nanny Angel Network (nan), a free childcare service for mothers undergoing cancer treatment.Methods All 243 living mothers who had used the nan service were invited by telephone to participate in an online research survey; 197 mothers (81%) consented to participate. The survey, sent by e-mail, consisted of 39 items divided into these categories: demographics, supports, use, satisfaction, and general comments. ResultsOf the 197 moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Other barriers such as having inadequate childcare and having to pay for childcare have been associated with a lack of breast cancer screening (Balas et al., 2020). Although research is limited on addressing childcare as a screening barrier, one study of the Canadian-based Nanny Angel Network , a free childcare charitable organization for mothers with cancer, showed that women with cancer are more likely to use these services if available (Cohen et al., 2017). Programs like the Nanny Angel Network offer potential models that can be explored and tailored to communities in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Other barriers such as having inadequate childcare and having to pay for childcare have been associated with a lack of breast cancer screening (Balas et al., 2020). Although research is limited on addressing childcare as a screening barrier, one study of the Canadian-based Nanny Angel Network , a free childcare charitable organization for mothers with cancer, showed that women with cancer are more likely to use these services if available (Cohen et al., 2017). Programs like the Nanny Angel Network offer potential models that can be explored and tailored to communities in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses play an important role in the treatment of children with dry eye; they not only perform clinical nursing work, but also play an important role in enhancing the child's mood, mentality, and safety. As a special medical group, nursing staff should pay close attention to children's physical diseases as well as their psychological reactions to the treatment process (15). In the process of child care, "people- oriented" is the core concept of nursing, which involves more patience and care ( 16), and will help to improve the treatment compliance of children and facilitate the building of a harmonious relationship between nurses and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that the di culty associated with coordinating childcare and health care appointments contributes to role strain, frustration, and appointment noncompliance for patients [7-8, 10, 13]. To our knowledge, only one study has speci cally assessed childcare needs in cancer patients and the success of a supportive childcare intervention [13]. This study, conducted by Cohen et al, found that over 50% of mothers considered childcare to be their most overwhelming responsibility after their cancer diagnosis, and 75% indicated that a supportive childcare intervention allowed them to keep appointments that they would have otherwise had to miss [13].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only one study has speci cally assessed childcare needs in cancer patients and the success of a supportive childcare intervention [13]. This study, conducted by Cohen et al, found that over 50% of mothers considered childcare to be their most overwhelming responsibility after their cancer diagnosis, and 75% indicated that a supportive childcare intervention allowed them to keep appointments that they would have otherwise had to miss [13]. On-site childcare also has the potential bene t of convenience for patients and the ability to link families in with other oncology services.…”
Section: Introductionmentioning
confidence: 99%